Design of CSDG MOSFET based low noise amplifier for GHZ range - Luthuli, Lwazi; Srivastava, Viranjay M. (International Journal of Engineering and Technology, 2018)
In this paper we have presented a Cylindrical Surrounding Double-Gate (CSDG) MOSFET based Low Noise Amplifier (LNA) that operates at frequencies from 1 GHz to 10 GHz. The designed CSDG based LNA is combination of conventional LNA with CSDG MOSFET for low noise figure at high frequencies. The CSDG MOSFET comprises of both the main and active feedback transistor. The highest gain achieved is -16 dB at 2.4 GHz. The stability factor K greater than 1 and the achieved lowest noise figure is 0.2 dB at 10 GHz. The proposed designed LNA provides the lowest noise figure at the highest frequencies compared to other conventional LNAs.